Forensic Analysis of UAV DJI MINI 3 and Non-rooted RC-N1 Android Smartphone Using DRF Framework - Muhammad Yusuf Halim; Ahmad Luthfi (Department of Informatics Engineering, Universitas Muhammadiyah Purwokerto, 2025)
The increasing use of Unmanned Aerial Vehicles across various sectors also raises potential misuse, such as unauthorized surveillance and airspace violations. This research aims to analyze digital artefacts from UAV DJI Mini 3 and Android Smartphone Controller (DJI RC-N1) using the DRF Field forensic framework. Data acquisition was performed through static and dynamic methods on the UAV and both physical and logical methods on the smartphone, without rooting the device. The analysis reveals that dynamic acquisition on the UAV provides geotagged EXIF images, including latitude, longitude, and altitude information. Meanwhile, flight log data were not found on the UAV but were successfully retrieved from the smartphone via logical acquisition by identifying the DJI Fly application package (dji.go.v5). The extracted flight logs were then processed into .kmz format using Phantomhelp.com and visualized through Google Earth to confirm airspace violations. This study highlights that all forensic acquisition was conducted without rooting, ensuring device integrity and legal admissibility.